Novel lead compounds in pre-clinical development against African sleeping sickness. Issue 10 (4th August 2017) - Berninger, Michael; Schmidt, Ines; Ponte-Sucre, Alicia; Holzgrabe, Ulrike
Abstract : This article reviews the recent progress in drug development against the African sleeping sickness. Abstract : Human African trypanosomiasis (HAT), also known as African sleeping sickness, is caused by parasitic protozoa of the genus Trypanosoma . As the disease progresses, the parasites cross the blood brain barrier and are lethal for the patients if the disease is left untreated. Current therapies suffer from several drawbacks due to e.g. toxicity of the respective compounds or resistance to approved antitrypanosomal drugs. In this review, the different strategies of drug development against HAT are considered, namely the target-based approach, the phenotypic high throughput screening and the drug repurposing strategy. The most promising compounds emerging from these approaches entering an in vivo evaluation are mentioned herein. Of note, it may turn out to be difficult to confirm in vitro activity in an animal model of infection; however, possible reasons for the missing efficacy in unsuccessful in vivo studies are discussed.